2005
DOI: 10.1080/08860220500244823
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate Causes Oxidative Stress in Rat Kidney Tissues

Abstract: It has been suggested that MTX leads to oxidative stress in rat kidney tissues, which might be one of the reasons for MTX-induced nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 20 publications
1
35
0
1
Order By: Relevance
“…The pathogenesis of Mtx nephrotoxicity involves multiple pathways, including oxidative stress and inflammation (Devrim et al, 2005;Asvadi et al, 2011). Inflammatory mediators including TNF-α, IL-1 and NO, known as endothelium-derived relaxing factor (EDRF) are shown to play important roles in the pathogenesis of Mtx nephrotoxicity (Ibrahim et al, 2014;Kirbas et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of Mtx nephrotoxicity involves multiple pathways, including oxidative stress and inflammation (Devrim et al, 2005;Asvadi et al, 2011). Inflammatory mediators including TNF-α, IL-1 and NO, known as endothelium-derived relaxing factor (EDRF) are shown to play important roles in the pathogenesis of Mtx nephrotoxicity (Ibrahim et al, 2014;Kirbas et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that oxidative stress and inflammation may have role inthe pathogenesis of MTX-induced nephrotoxicity rather than blockage in folate synthesis in kidneys (Devrim et al, 2005;Asvadi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The results of biochemical tests showed a significant increase in the liver tissue of the MTXC group in the levels of oxidant parameters, e.g., MDA and MPO, and a decrease in anti-oxidant parameters, e.g., GSH and SOD. Oxidative stress is implicated in methotrexate toxicity in the liver 11 . Oxidative stress is an indicator of the damage that results from a change in the balance between oxidants and anti-oxidants in favour of oxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were parallel to some studies which indicated, the after MTX intoxication, significant depletion of the GSH level and also significant decreases in activities of SOD, CAT and GPx was evidenced, corroborating the state of oxidative stress. 23,32,33 MDA is one of the most commonly markers of lipid peroxidation. Lipid peroxidation is a wellknown mechanism of cellular injury in the human body.…”
Section: Discussionmentioning
confidence: 99%